Foreign Aid with and without Dollar Shortage - Mendershausen, Horst (The Review of Economics and Statistics, 1951)
DURING the period of the European Recovery Program (ERP), the first large scale provision of foreign aid by the United States in peacetime has been experienced. Foreign aid did not begin with ERP, and it may continue to exist as a general institution well beyond the duration of that particular program. But the practice of foreign aid outside times of acute national emergency required a deeper search for its rationale. The attention of policy makers and students came to be focused on the dollar shortage. The dollar shortage of foreign countries served as an explanation of the need for our aid, and its computation served as a means for establishing the amount of aid required. The search for an explanation of foreign aid in peacetime has suffered somewhat from the fact that the extraordinary situation of aid to Europe was not considered a part of a series of extraordinary situations that have been with us almost continually since 1940. The general problem of our foreign aid, its apparently prominent place in our scheme of things, was not sufficiently clear. It seemed necessary to rediscover some of the broader insights gained in World War II, especially during the great Lend-Lease discussion, regarding the nature of the relations between the United States and certain groupings of foreign countries. At the same time, it became apparent that it was necessary to distinguish between various phases of foreign aid which are characterized by different approaches. The dollar shortage is merely one line of approach. The dollar shortage is understood here as a particular process of foreign aid administration. This is not offered as a novel definition but rather as an attempt to catch the common meaning of the term in the time when it appeared and became operational in international economics. In particular, it seems useful to use the term not merely as a synonym for either United States foreign aid or a United States export surplus. Two Viewpoints on Dollar Shortage